The National Pain Audit for specialist pain services in England and Wales 2010–2014. Issue 3 (August 2019) - Price, Cathy; de C Williams, Amanda C; Smith, Blair H; Bottle, Alex
Introduction: Numerous reports highlight variations in pain clinic provision between services, particularly in the provision of multidisciplinary services and length of waiting times. A National Audit aims to identify and quantify these variations, to facilitate raising standards of care in identified areas of need. This article describes a Quality Improvement Programme cycle covering England and Wales that used such an approach to remedy the paucity of data on the current state of UK pain clinics. Methods: Clinics were audited over a 4-year period using standards developed by the Faculty of Pain Medicine of The Royal College of Anaesthetists. Reporting was according to guidance from a recent systematic review of national surveys of pain clinics. A range of quality improvement measures was introduced via a series of roadshows led by the British Pain Society. Results: 94% of clinics responded to the first audit and 83% responded to the second. Per annum, 0.4% of the total national population was estimated to attend a specialist pain service. A significant improvement in multidisciplinary staffing was found (35–56%, p < 0.001) over the 4-year audit programme, although this still requires improvement. Very few clinics achieved recommended evidence-based waiting times, although only 2.5% fell outside government targets; this did not improve. Safety standards were generally met. Clinicians often failed to code diagnoses. Conclusion: A National Audit found that while generally safe many specialist pain services in England and Wales fell below recommended standards of care. Waiting times and staffing require improvement if patients are to get effective and timely care. Diagnostic coding also requires improvement.